PVA film and preparation method thereof

By mixing conventional PVA with modified PVA and performing acid crosslinking reactions in the production of PVA films, the problem of using toxic chemical crosslinking agents in the prior art is solved, and the water resistance of PVA films is improved and the environmental protection requirements are met.

CN119708567APending Publication Date: 2025-03-28ANHUI WANWEI ADVANCED FUNCTIONAL MEMBRANE MATERIALS RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411906103.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Chemical crosslinking agents used in the prior art, such as glutaraldehyde, have irritating odors and toxicity, and it is difficult to achieve environmental protection requirements during the production and use of PVA films.

Method used

By mixing conventional PVA with modified PVA and cross-linking reactions under an acidic environment, a cross-linking network structure is formed to improve the water resistance of the PVA film, and the use of toxic and odorous chemical cross-linking agents is avoided.

Benefits of technology

The water resistance of PVA film is improved, while avoiding the use of toxic substances. The resulting PVA film is odor-free, environmentally friendly, biodegradable, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708567A_ABST
    Figure CN119708567A_ABST
Patent Text Reader

Abstract

The invention discloses a PVA (polyvinyl alcohol) film and a preparation method thereof, and relates to the technical field of PVA, the method comprises the following steps: mixing a mixture of conventional PVA and modified PVA, a plasticizer and deionized water, stirring for swelling, and heating for dissolving to obtain a mixed solution; adding an acidic reagent and a sodium hydroxide solution into the mixed solution, adjusting the pH value of the mixed solution to 1-5, and stirring to carry out a cross-linking reaction to obtain a reaction solution; coating with the reaction liquid to form a film, and drying to obtain a PVA film; the modified PVA contains a large number of carbonyl groups and can be subjected to a cross-linking reaction with hydrophilic hydroxyl groups in conventional PVA under an acidic condition, on one hand, the content of hydrophilic hydroxyl groups in the conventional PVA can be reduced, the water resistance of the conventional PVA can be improved, on the other hand, a cross-linking network structure is formed between the conventional PVA and the modified PVA through the cross-linking reaction, the intermolecular acting force of the conventional PVA and the modified PVA can be enhanced, and the water resistance of the conventional PVA is improved. The water resistance is further improved; and the obtained PVA film is non-toxic, environment-friendly and high in biodegradability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of PVA, and in particular to a PVA film and a preparation method thereof. Background Art

[0002] Polyvinyl alcohol (PVA) is one of the common polymer materials. The film made of PVA has the advantages of being non-toxic and odorless, high transparency, good gas barrier properties, dust-free and good mechanical properties. According to the application requirements of PVA, it can be divided into two categories: low-temperature fast-dissolving PVA film and high-temperature water-resistant PVA film. Among them, high-temperature water-resistant PVA film has broad application prospects in the fields of oil-water separation, sewage treatment, biomedical materials, etc. Research on the water resistance modification of PVA film has extremely high economic and social benefits.

[0003] PVA has a strong affinity for water because it contains a large number of hydrophilic hydroxyl groups in its molecular structure. Cross-linking is currently the main method for modifying the water resistance of PVA film. Its main mechanism is that the hydrophilic hydroxyl groups on the PVA molecular chain react with small molecule cross-linking agents in an acidic environment, reducing the hydroxyl content in the PVA molecular structure while forming a cross-linked network structure to improve the water resistance of the film. However, the chemical cross-linking agents used in the current cross-linking method, such as glutaraldehyde and glyoxal, have pungent odors and toxicity, which are easy to cause pollution during the production and use of the film, and do not meet the requirements of green environmental protection. Summary of the invention

[0004] The object of the present invention is to provide a PVA film and a preparation method thereof, to solve the following technical problems:

[0005] How to improve the water resistance of PVA film in a more environmentally friendly way?

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] In a first aspect, the present invention discloses a method for preparing a PVA film, comprising the following steps:

[0008] S1. Mix a PVA mixture, a plasticizer and deionized water, stir and swell, and then heat to dissolve to obtain a mixed solution; wherein the PVA mixture is a mixture of conventional PVA and modified PVA, the conventional PVA is commercially available unmodified ordinary PVA, and the modified PVA is prepared by a green micro-swelling method for preparing modified polyvinyl alcohol disclosed in the patent document with publication number CN118599036A, so it is not repeated in the present invention. The modified PVA prepared by oxidative modification by this method contains a large amount of carbonyl groups and is non-toxic and environmentally friendly;

[0009] S2, adding an acidic reagent and a sodium hydroxide solution to the mixed solution, adjusting the pH of the mixed solution to 1-5, and stirring to perform a cross-linking reaction to obtain a reaction solution;

[0010] S3. Use the reaction solution to form a film and then dry it to obtain a PVA film.

[0011] Preferably, in step S1, in parts by weight, the PVA mixture is 10-30 parts, the plasticizer is 10-30 parts, and the deionized water is 100 parts.

[0012] Preferably, in step S1, the mixture of conventional PVA and modified PVA has an average degree of polymerization of 1500-2400, an average degree of alcoholysis of 86%-99%, and a carbonyl content of 10%-30%.

[0013] Conventional PVA has a low carbonyl content and a high hydroxyl content, while modified PVA contains a large number of carbonyl groups, which can undergo cross-linking reaction with the hydrophilic hydroxyl groups in conventional PVA under acidic conditions. The reaction formula is as follows: Figure 1 As shown, on the one hand, the content of hydrophilic hydroxyl groups in conventional PVA can be reduced and its water resistance can be improved. On the other hand, the cross-linking reaction forms a cross-linked network structure between conventional PVA and modified PVA, which can enhance the intermolecular force between the two and further improve the water resistance.

[0014] When determining whether the carbonyl content of the PVA mixture meets the standard for raw material selection, the carbonyl content of the mixture is tested by the following steps:

[0015] a. Dry the PVA mixture sample in a 60°C oven for 48 hours to constant weight, accurately weigh 1.0 g of the PVA mixture sample and place it in a 250 mL ground-mouth conical flask;

[0016] b. Add 100 ml of deionized water, heat at 95 ° C to completely dissolve the PVA mixture sample, cool to 40 ° C, add 1% thymol blue as an indicator, and then adjust the pH value to 2.8 with 0.1 mol / L hydrochloric acid solution to obtain a mixed solution;

[0017] c. Add 20-40 mL of hydroxylamine hydrochloride solution to the mixture and stir at room temperature for 4 h;

[0018] d. Titrate the above solution with 0.1 mol / L hydrochloric acid solution to pH 2.8. At this time, the indicator turns yellow again. Calculate the carbonyl content in the sample according to the following formula:

[0019]

[0020] Among them, V bis the amount of hydrochloric acid used when the unoxidized modified PVA is used as the reference sample, Vs is the amount of hydrochloric acid used when the oxidized modified PVA is used as the sample, C HCl is the concentration of hydrochloric acid, and m is the sample in the solution.

[0021] Preferably, in step S1, the plasticizer is a small molecule alcohol, a polyol, a polyol ester, and / or; wherein the small molecule alcohol is ethylene glycol, propylene glycol, glycerol, pentaerythritol, and / or; the polyol is polyethylene glycol, polypropylene glycol, polyglycerol, and / or; the polyol ester is ethylene glycol ester and glyceride compound, and / or.

[0022] Preferably, in step S1, the parameters of the stirring swelling are: stirring rate of 100-300 r / min, swelling temperature of 20-50°C, swelling time of 0.5-2h; the parameters of the heating dissolution are: heating temperature of 85-95°C, dissolution time of 40min-3h.

[0023] Preferably, in step S2, the acidic reagent is any one of hydrochloric acid, sulfuric acid, phosphoric acid and acetic acid, and the mass fraction of the acidic reagent is 3%-15%.

[0024] Preferably, in step S2, the concentration of the sodium hydroxide solution is 1 mol / L.

[0025] Preferably, in step S2, the temperature of the cross-linking reaction is 50-80°C, the time is 2-4h, and the stirring rate is 100-300r / min.

[0026] Preferably, in step S3, the drying temperature is 60-95° C. and the drying time is 5-15 min.

[0027] In a second aspect, the present invention also discloses a PVA film, which is prepared by the preparation method of the PVA film as described above, and has the characteristics of water resistance, biodegradability, no odor, high mechanical strength, and no addition of organic substances such as glutaraldehyde during the preparation process, and has a wide range of application scenarios.

[0028] Since no toxic or harmful substances are added during the processing of the PVA film, it can be used in food packaging such as ordinary / vacuum food packaging, sausage casings, etc. It can also be used as clothing packaging film, agricultural mulch film and greenhouse film, electronic product coating film, medical packaging bags, etc.

[0029] Based on the good water resistance and high biodegradability of the PVA film, it can be used in environmentally friendly stretch packaging self-adhesive films and wastewater treatment filter membranes. It can also be used to prepare non-toxic polyvinyl alcohol degradable antibacterial packaging films by adding antibacterial agents.

[0030] The PVA film can also be used in medical bionic stents, hoses, 3D printing materials, toys, models and other products.

[0031] Beneficial effects of the present invention:

[0032] 1. The PVA film of the present invention contains conventional PVA and modified PVA. Conventional PVA has a very low carbonyl content and a high hydroxyl content, while modified PVA contains a large number of carbonyl groups, which can undergo a cross-linking reaction with the hydrophilic hydroxyl groups in conventional PVA under acidic conditions. On the one hand, the content of hydrophilic hydroxyl groups in conventional PVA can be reduced, thereby improving its water resistance. On the other hand, the cross-linking reaction forms a cross-linked network structure between conventional PVA and modified PVA, thereby enhancing the intermolecular force between the two and further improving the water resistance.

[0033] 2. In the preparation method of the PVA film of the present invention, acidic reagents such as hydrochloric acid and phosphoric acid are directly used to create an acidic environment for conventional PVA and modified PVA, so that the two undergo a cross-linking reaction, thereby avoiding the use of toxic and odorous reagents such as glutaraldehyde. In addition, the modified PVA raw material is also a non-toxic and odorless substance obtained by oxidative modification of conventional PVA. Therefore, the obtained PVA film is non-toxic, environmentally friendly, and highly biodegradable.

[0034] 3. The preparation method of the PVA film of the present invention has the characteristics of simple operation and stable reaction. The modified PVA's own carbonyl group is used to cross-link with conventional PVA, thereby avoiding the phenomenon of reaction failure caused by reaction explosion when using a small molecule cross-linking agent, which is more conducive to the large-scale stable production of PVA film. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The present invention will be further described below in conjunction with the accompanying drawings.

[0036] Figure 1 It is a reaction diagram of the cross-linking reaction between conventional PVA and modified PVA in the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0039] For example, the PVA mixture in the following embodiments and comparative examples is a mixture obtained by mixing conventional PVA and modified PVA in different proportions, wherein the conventional PVA is derived from Anhui Wanwei High-tech Materials Co., Ltd., and the modified PVA is self-made by a green micro-swelling method for preparing modified polyvinyl alcohol disclosed in the patent document with publication number CN118599036A.

[0040] Example 1

[0041] A mixture of 100 parts of deionized water, 10 parts of propylene glycol, 10 parts of polyethylene glycol and 20 parts of PVA (average degree of polymerization 2000, average degree of alcoholysis 90%, carbonyl content 20%) was stirred and swollen at 30°C at a stirring rate of 150 r / min for 1 hour, then heated to 90°C for dissolution for 3 hours, 10% hydrochloric acid solution by mass and 1 mol / mL sodium hydroxide solution were added to adjust the pH to 3, the temperature was lowered to 65°C and the reaction was continued at a stirring rate of 150 r / min for 3 hours. After the reaction was completed, the product was poured into a beaker, then coated into a film, and dried at 70°C for 10 minutes to obtain a PVA film with a thickness of 60 um.

[0042] Example 2

[0043] A mixture of 100 parts of deionized water, 10 parts of propylene glycol, 10 parts of polyethylene glycol and 11 parts of PVA (average degree of polymerization 2000, average degree of alcoholysis 90%, carbonyl content 10%) was stirred and swollen at 30°C at a stirring rate of 150 r / min for 1 hour, then heated to 90°C for dissolution for 3 hours, 10% hydrochloric acid solution by mass and 1 mol / mL sodium hydroxide solution were added to adjust the pH to 3, the temperature was lowered to 50°C and the reaction was continued at a stirring rate of 150 r / min for 3 hours. After the reaction was completed, the product was poured into a beaker, then coated into a film, and dried at 70°C for 10 minutes to obtain a PVA film with a thickness of 60 um.

[0044] Example 3

[0045] A mixture of 100 parts of deionized water, 10 parts of propylene glycol, 10 parts of polyethylene glycol and 30 parts of PVA (average degree of polymerization 1700, average degree of alcoholysis 90%, carbonyl content 30%) was stirred and swollen at 30°C at a stirring rate of 150 r / min for 1 hour, then heated to 90°C for dissolution for 3 hours, 10% hydrochloric acid solution by mass and 1 mol / mL sodium hydroxide solution were added to adjust the pH to 3, the temperature was lowered to 80°C and the reaction was continued at a stirring rate of 150 r / min for 3 hours. After the reaction was completed, the product was poured into a beaker, then coated into a film, and dried at 70°C for 10 minutes to obtain a PVA film with a thickness of 60 um.

[0046] Example 4

[0047] A mixture of 100 parts of deionized water, 5 parts of propylene glycol, 5 parts of polyethylene glycol and 20 parts of PVA (average degree of polymerization 1500, average degree of alcoholysis 86%, carbonyl content 20%) was stirred and swollen at 30°C at a stirring rate of 150 r / min for 1 hour, then heated to 90°C for dissolution for 3 hours, 10% hydrochloric acid solution by mass and 1 mol / mL sodium hydroxide solution were added to adjust the pH to 3, the temperature was lowered to 50°C and the reaction was continued at a stirring rate of 150 r / min for 5 hours. After the reaction was completed, the product was poured into a beaker, then coated into a film, and dried at 70°C for 15 minutes to obtain a PVA film with a thickness of 60 um.

[0048] Example 5

[0049] A mixture of 100 parts of deionized water, 5 parts of propylene glycol, 5 parts of polyethylene glycol, and 24 parts of PVA (average degree of polymerization 2400, average degree of alcoholysis 99%, carbonyl content 25%) was stirred and swollen at 30°C at a stirring rate of 150 r / min for 1 hour, then heated to 90°C for dissolution for 3 hours, 10% hydrochloric acid solution by mass and 1 mol / mL sodium hydroxide solution were added to adjust the pH to 3, the temperature was lowered to 50°C and the reaction was continued at a stirring rate of 150 r / min for 3 hours. After the reaction was completed, the product was poured into a beaker, then coated into a film, and dried at 70°C for 15 minutes to obtain a PVA film with a thickness of 60 um.

[0050] Example 6

[0051] A mixture of 100 parts of deionized water, 15 parts of propylene glycol, 15 parts of polyethylene glycol, and 20 parts of PVA (average degree of polymerization 2000, average degree of alcoholysis 90%, carbonyl content 20%) was stirred and swollen at 30°C at a stirring rate of 150 r / min for 1 hour, then heated to 90°C for dissolution for 3 hours, 10% hydrochloric acid solution by mass and 1 mol / mL sodium hydroxide solution were added to adjust the pH to 1, the temperature was lowered to 50°C and the reaction was continued at a stirring rate of 150 r / min for 3 hours. After the reaction was completed, the product was poured into a beaker, then coated into a film, and dried at 70°C for 15 minutes to obtain a PVA film with a thickness of 60 um.

[0052] Example 7

[0053] A mixture of 100 parts of deionized water, 15 parts of propylene glycol, 15 parts of polyethylene glycol, and 20 parts of PVA (average degree of polymerization 2000, average degree of alcoholysis 90%, carbonyl content 20%) was stirred and swollen at 30°C at a stirring rate of 150 r / min for 1 hour, then heated to 90°C for dissolution for 3 hours, 10% hydrochloric acid solution by mass and 1 mol / mL sodium hydroxide solution were added to adjust the pH to 5, the temperature was lowered to 50°C and the reaction was continued at a stirring rate of 150 r / min for 3 hours. After the reaction was completed, the product was poured into a beaker, then coated into a film, and dried at 70°C for 15 minutes to obtain a PVA film with a thickness of 60 um.

[0054] Example 8

[0055] A mixture of 100 parts of deionized water, 15 parts of propylene glycol, 15 parts of polyethylene glycol, and 20 parts of PVA (average degree of polymerization 2000, average degree of alcoholysis 90%, carbonyl content 20%) was stirred and swollen at 50°C at a stirring rate of 100 r / min for 0.5 h, then heated to 90°C to dissolve for 3 h, 10% hydrochloric acid solution by mass and 1 mol / mL sodium hydroxide solution were added to adjust the pH to 3, the temperature was lowered to 50°C and the reaction was continued at a stirring rate of 300 r / min for 2 h. After the reaction was completed, the product was poured into a beaker, then coated into a film, and dried at 60°C for 15 min to obtain a PVA film with a thickness of 60 um.

[0056] Example 9

[0057] A mixture of 100 parts of deionized water, 15 parts of propylene glycol, 15 parts of polyethylene glycol and 20 parts of PVA (average degree of polymerization 2000, average degree of alcoholysis 90%, carbonyl content 20%) was stirred and swollen at 20°C at a stirring rate of 300 r / min for 2 hours, then heated to 90°C to dissolve for 3 hours, 10% hydrochloric acid solution by mass and 1 mol / mL sodium hydroxide solution were added to adjust the pH to 3, the temperature was lowered to 80°C and the reaction was continued at a stirring rate of 100 r / min for 4 hours. After the reaction was completed, the product was poured into a beaker, coated into a film, and dried at 95°C for 5 minutes to obtain a PVA film with a thickness of 60 um.

[0058] Comparative Example 1

[0059] Compared with Example 1, the only difference is that the modified PVA is replaced by unmodified conventional PVA (the average polymerization degree of the mixture of polyethylene glycol and conventional PVA is 2000 and the average alcoholysis degree is 90%), and the other conditions are exactly the same as the steps, and finally a PVA film with a thickness of 60um is obtained.

[0060] Comparative Example 2

[0061] Compared with Example 1, the only difference is that the average polymerization degree of the mixture of polyethylene glycol and conventional PVA is 2000, the average alcoholysis degree is 90%, and the carbonyl content is 8%. Other conditions are exactly the same as the steps, and a PVA film with a thickness of 60 um is finally obtained.

[0062] Comparative Example 3

[0063] Compared with Example 1, the only difference is that the hydrochloric acid solution with a mass fraction of 10% and the sodium hydroxide solution with a concentration of 1 mol / mL are not added to adjust the pH to 3. The other conditions are exactly the same as the steps, and finally a PVA film with a thickness of 60 um is obtained.

[0064] Comparative Example 4

[0065] Compared with Example 1, the only difference is that the reaction time is 1 hour, and the other conditions and steps are exactly the same, and finally a PVA film with a thickness of 60 um is obtained.

[0066] The moisture content, gas permeability and solubility of the PVA films prepared in Examples 1-9 and Comparative Examples 1-4 were tested respectively, and the testing method was as follows:

[0067] Moisture content: refer to JIS-K-6726-1994;

[0068] Gas permeability: refer to GBT1038.1-2022;

[0069] Solubility: add 1L pure water of corresponding temperature (60 / 80 / 90℃) into a 1L beaker, adjust the rotation speed to 200r / min; cut the prepared PVA film into film samples with a length and width of 5cm*5cm, fix the film samples in a fixture, immerse them in water and time them synchronously, record the disintegration time (the water-soluble film will not disintegrate if one corner falls off or the middle is damaged) and the complete dissolution time; each group of samples is tested three times in parallel, and the solubility of the water-soluble film and packaging materials is recorded.

[0070] The test results of moisture content and gas permeability are listed in Table 1. Table 1 is as follows:

[0071] Table 1

[0072]

[0073] By analyzing the data in Table 1, it can be learned that, when the moisture content is the same, the gas permeability of the PVA film prepared in Examples 1-9 is significantly lower than that in Comparative Examples 1-4.

[0074] The solubility test results are listed in Table 2, which is as follows:

[0075] Table 2

[0076]

[0077]

[0078] By analyzing the data in Table 2, it can be seen that compared with Comparative Examples 1-4, the water solubility of the PVA films prepared in Examples 1-9 is significantly better, indicating that the water resistance is stronger.

[0079] The above describes several embodiments of the present invention in detail, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a PVA film, characterized in that: The steps include: S1, mixing a PVA mixture, a plasticizer, and deionized water, stirring to swell, and then heating to dissolve to obtain a mixed solution, wherein the PVA mixture is a mixture of conventional PVA and modified PVA; S2, adding an acidic reagent and a sodium hydroxide solution to the mixed solution, adjusting the pH of the mixed solution to 1-5, and stirring to perform a cross-linking reaction to obtain a reaction solution; S3. Use the reaction solution to form a film and then dry it to obtain a PVA film.

2. The method for preparing a PVA film according to claim 1, characterized in that: In step S1, in parts by weight, the PVA mixture is 10-30 parts, the plasticizer is 10-30 parts, and the deionized water is 100 parts.

3. The method for preparing the PVA film according to claim 1, characterized in that: In step S1, the PVA mixture has an average degree of polymerization of 1500-2400, an average degree of alcoholysis of 86%-99%, and a carbonyl content of 10%-30%.

4. The method for preparing a PVA film according to claim 1, characterized in that: In step S1, the plasticizer is a small molecule alcohol, a polyol, a polyol ester, and / or; wherein the small molecule alcohol is ethylene glycol, propylene glycol, glycerol, pentaerythritol, and / or; the polyol is polyethylene glycol, polypropylene glycol, polyglycerol, and / or; the polyol ester is ethylene glycol ester and glyceride compound, and / or.

5. The method for preparing the PVA film according to claim 1, characterized in that: In step S1, the parameters of the stirring swelling are: stirring rate of 100-300 r / min, swelling temperature of 20-50°C, swelling time of 0.5-2h; the parameters of the heating dissolution are: heating temperature of 85-95°C, dissolution time of 40min-3h.

6. The method for preparing a PVA film according to claim 1, characterized in that: In step S2, the acidic reagent is any one of hydrochloric acid, sulfuric acid, phosphoric acid and acetic acid, and the mass fraction of the acidic reagent is 3%-15%.

7. The method for preparing a PVA film according to claim 1, characterized in that: In step S2, the concentration of the sodium hydroxide solution is 1 mol / L.

8. The method for preparing a PVA film according to claim 1, characterized in that: In step S2, the cross-linking reaction is carried out at a temperature of 50-80°C, for a time of 2-4 hours, and at a stirring rate of 100-300 r / min.

9. The method for preparing a PVA film according to claim 1, characterized in that: In step S3, the drying temperature is 60-95°C and the drying time is 5-15 minutes.

10. A PVA film, characterized in that: The PVA film is prepared by the method for preparing a PVA film according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Green micro-swelling method for preparing modified polyvinyl alcohol

    CN118599036A